O USO DE TECNOLOGIAS DE INFORMAÇÃO E COMUNICAÇÃO NO ENSINO DE MOVIMENTOS EM DUAS DIMENSÕES. LANÇAMENTO DE FOGUETES. - Orkiel, Edenilson (2016)
In this work the intention was to teach the content structuring movements in two dimensions, addressing the concepts related to the uniform motion, accelerated and oblique with the construction and use of simple experiments for it. In this sense, it was built with the student’s rocket powered by water and compressed air, as well as other types of experiments demonstrating the movement of objects making up the record video for later analysis with the help of Tracker computer program. Tracker program is used as a facilitator in the understanding of the concepts related to uniform, accelerated movement as well as movements in two dimensions’ composition or oblique movement. Within these activities, the purpose was to enable students to classes that allow understanding of how to build physical models of motion and the equations that describe them, aiming to make sense of the physical concepts taught. One example is through the Tracker program, enabling students graphing activities of the movements, as well as analysis and interpretation correlating with what has been seen in practice. After analyzing the results, it could be observed that the different classes with the use of ICT, the Tracker program and experiments built by the students themselves, contributed to the motivation and interest in the subject taught at the same time that the road to learning it was easier to reach the success of the proposal.